High-density high-thermal-conductivity quartz crucible and preparation method thereof
By adding nanoalumina and carbon nanotubes to the preparation process of quartz crucibles, and eliminating air holes with high pressure isostatic pressure treatment, the performance problems caused by vents in traditional quartz crucibles are solved, and a high density and high heat conductivity quartz crucible is realized, which is suitable for high temperature experiments and material synthesis.
Patent Information
- Application Number
- CN202411759998.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-28
AI Technical Summary
Traditional quartz crucibles are prone to form internal pores during the preparation process, resulting in reduced density, mechanical strength and thermal conductivity, insufficient structural stability, and uneven heat conduction, which affects the efficiency and safety of high-temperature operation.
High-purity quartz sand, binder, nano-alumina and carbon nanotubes are mixed in proportion, and an opaque layer is formed after pressing and natural drying. The transparent layer is then coated and high-pressure isostatic treatment is performed to eliminate pores and promote material phase change, and finally polish and coat high-temperature resistant coating.
It improves the mechanical strength, thermal conductivity and chemical stability of the quartz crucible, ensures stability and reliability under high temperature conditions, enhances the density and thermal conductivity of the crucible, and is suitable for high-temperature experiments and material synthesis.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of crucibles, and in particular to a high-density and high-thermal-conductivity quartz crucible and a preparation method thereof. Background Art
[0002] Quartz crucible is a high-temperature resistant furnace vessel made of high-purity quartz. It is widely used in metal smelting, material analysis and chemical experiments. Its excellent heat resistance and chemical stability enable it to maintain structural integrity in high temperature environments and not react with samples. This crucible is widely used in metal smelting, material analysis and ceramic sintering. Quartz crucible not only has excellent thermal stability, but also has good corrosion resistance, which can effectively prevent sample contamination.
[0003] The traditional crucible preparation process often forms pores inside the material. The large distribution of pores will have a negative impact on the overall performance of the crucible, including reducing its density, mechanical strength and thermal conductivity, weakening the structural stability of the crucible, and causing it to be easy to break or damage in a high-temperature environment. At the same time, the uneven distribution of pores will also hinder the uniform conduction of heat, affecting the efficiency and safety of the crucible in high-temperature operation. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a high-density and high-thermal-conductivity quartz crucible to solve the problems raised in the above background technology.
[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing a high-density and high-thermal-conductivity quartz crucible, comprising the following steps:
[0006] S1. Put high-purity quartz sand, binder, nano-alumina and carbon nanotubes into a blender in proportion and mix them, and add an appropriate amount of deionized water to obtain an opaque layer mixture;
[0007] S2, pressing the opaque layer mixture using a pressing device, applying a pressure of 35 MPa, maintaining for 2 minutes, then demolding, and drying naturally to obtain an opaque layer;
[0008] S4, putting high-purity quartz powder and a binder into a blender according to a certain proportion, and adding deionized water to obtain a transparent layer mixture;
[0009] S5, uniformly coating the transparent layer mixture on the inner wall of the opaque layer and pressing it with a pressing device, and drying it naturally to obtain an initial quartz crucible;
[0010] S6, placing the initial crucible into a closed cavity of a high-pressure isostatic pressing device, applying an isostatic pressure of 50 MPa-200 MPa while heating the cavity for 4 hours and gradually cooling to room temperature;
[0011] S7. Polishing the transparent layer and the opaque layer of the quartz crucible, and coating the layer with a high temperature resistant coating after polishing to form a coating with a thickness of about 1-2 mm, and obtaining the quartz crucible after natural drying.
[0012] Preferably, in S1, the purity of the high-purity quartz sand is not less than 99.9%, the particle size of the nano-alumina is less than 50 nm, and the content of the carbon nanotubes is 1-3% of the total mixture mass.
[0013] Preferably, in S1, high-purity quartz sand, binder, nano-alumina and carbon nanotubes are put into a blender and mixed in a ratio of 8:1.5:0.5:0.2.
[0014] Preferably, in S3, high-purity quartz powder and binder are put into a blender and mixed in a ratio of 9:1.
[0015] Preferably, in S6, the cooling control rate is 25°C / hour.
[0016] Preferably, in S6, during the cavity heating process, the temperature is increased to 1500°C-1700°C.
[0017] Preferably, in S7, the high temperature resistant coating is selected from one of zirconium-based ceramic coating, zirconium aluminate coating and silicon nitride coating.
[0018] Preferably, in the step S7, a polishing agent with a particle size of 0.5 μm is used during the polishing process of the transparent layer and the opaque layer of the quartz crucible.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: in the preparation process of the quartz crucible, the mechanical strength and thermal conductivity of the crucible are improved by adding nano-alumina, while the carbon nanotubes enhance the toughness and electrical conductivity of the material, ensuring stability and reliability under high temperature conditions; after the initial crucible is prepared, the high-pressure isostatic pressing equipment is used, which can not only eliminate the pores inside the crucible and increase the density, but also promote the phase change of the material at high temperature, so that the crucible has excellent thermal conductivity and chemical stability, so that the quartz crucible performs well in high-temperature experiments and material synthesis, meeting the needs of modern industry for high-performance ceramic materials. DETAILED DESCRIPTION
[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] An embodiment of the present invention provides a method for preparing a high-density and high-thermal-conductivity quartz crucible, comprising the following steps:
[0022] S1. Put high-purity quartz sand, binder, nano-alumina and carbon nanotubes into a blender in a ratio of 8:1.5:0.5:0.2, and add an appropriate amount of deionized water to obtain an opaque layer mixture.
[0023] Furthermore, the purity of the high-purity quartz sand is not less than 99.9%, the particle size of the nano-alumina is less than 50nm, and the content of the carbon nanotubes is 1-3% of the total mixture mass.
[0024] S2. The opaque layer mixture is pressed by a pressing device at a pressure of 35 MPa. After holding for 2 minutes, the mixture is demoulded and dried naturally to obtain an opaque layer.
[0025] S4. Put high-purity quartz powder and binder into a blender in a ratio of 9:1 and mix them, and add deionized water to obtain a transparent layer mixture.
[0026] S5. Evenly coating the transparent layer mixture on the inner wall of the opaque layer and pressing it with a pressing device, and drying it naturally to obtain an initial quartz crucible.
[0027] S6. Place the initial crucible into a sealed cavity of a high-pressure isostatic pressing device, heat the cavity while applying an isostatic pressure of 50 MPa-200 MPa for 4 hours and gradually cool to room temperature at a cooling control rate of 25°C / hour.
[0028] Furthermore, during the cavity heating process, the temperature rises to 1500°C-1700°C.
[0029] S7. Polishing the transparent layer and the opaque layer of the quartz crucible, and coating the layer with a high temperature resistant coating after polishing to form a coating with a thickness of about 1-2 mm, and obtaining the quartz crucible after natural drying.
[0030] Furthermore, the high temperature resistant coating is selected as one of zirconium-based ceramic coating, zirconium aluminate coating and silicon nitride coating. In addition, during the polishing process of the transparent layer and the opaque layer of the quartz crucible, a polishing agent with a particle size of 0.5 μm is used.
[0031] Embodiment 1
[0032] This embodiment provides a method for preparing a high-density and high-thermal-conductivity quartz crucible, comprising the following steps:
[0033] S1. Put high-purity quartz sand, binder, nano-alumina and carbon nanotubes into a blender in a ratio of 8:1.5:0.5:0.2, and add an appropriate amount of deionized water to obtain an opaque layer mixture.
[0034] Furthermore, the purity of the high-purity quartz sand is not less than 99.9%, the particle size of the nano-alumina is less than 50 nm, and the content of the carbon nanotubes is 1% of the total mixture mass.
[0035] S2. The opaque layer mixture is pressed by a pressing device at a pressure of 35 MPa. After holding for 2 minutes, the mixture is demoulded and dried naturally to obtain an opaque layer.
[0036] S4. Put high-purity quartz powder and binder into a blender in a ratio of 9:1 and mix them, and add deionized water to obtain a transparent layer mixture.
[0037] S5. Evenly coating the transparent layer mixture on the inner wall of the opaque layer and pressing it with a pressing device, and drying it naturally to obtain an initial quartz crucible.
[0038] S6. Place the initial crucible in a closed cavity of a high-pressure isostatic pressing device, heat the cavity and apply an isostatic pressure of 80 MPa for 4 hours and gradually cool to room temperature at a cooling control rate of 25°C / hour.
[0039] Furthermore, during the cavity heating process, the temperature rises to 1500°C.
[0040] S7. Polishing the transparent layer and the opaque layer of the quartz crucible, and coating the layer with a high temperature resistant coating after polishing to form a coating with a thickness of about 2 mm, and obtaining the quartz crucible after natural drying.
[0041] Furthermore, the high temperature resistant coating is selected as silicon nitride coating. In addition, during the polishing process of the transparent layer and the opaque layer of the quartz crucible, a polishing agent with a particle size of 0.5 μm is used.
[0042] Embodiment 2
[0043] This embodiment provides a method for preparing a high-density and high-thermal-conductivity quartz crucible, comprising the following steps:
[0044] S1. Put high-purity quartz sand, binder, nano-alumina and carbon nanotubes into a blender in a ratio of 8:1.5:0.5:0.2, and add an appropriate amount of deionized water to obtain an opaque layer mixture.
[0045] Furthermore, the purity of the high-purity quartz sand is not less than 99.9%, the particle size of the nano-alumina is less than 50 nm, and the content of the carbon nanotubes is 2% of the total mixture mass.
[0046] S2. The opaque layer mixture is pressed by a pressing device at a pressure of 35 MPa. After holding for 2 minutes, the mixture is demoulded and dried naturally to obtain an opaque layer.
[0047] S4. Put high-purity quartz powder and binder into a blender in a ratio of 9:1 and mix them, and add deionized water to obtain a transparent layer mixture.
[0048] S5. Evenly coating the transparent layer mixture on the inner wall of the opaque layer and pressing it with a pressing device, and drying it naturally to obtain an initial quartz crucible.
[0049] S6. Place the initial crucible in a closed cavity of a high-pressure isostatic pressing device, heat the cavity and apply an isostatic pressure of 150 MPa for 4 hours and gradually cool to room temperature at a cooling control rate of 25°C / hour.
[0050] Furthermore, during the cavity heating process, the temperature rises to 1500°C.
[0051] S7. Polishing the transparent layer and the opaque layer of the quartz crucible, and coating the layer with a high temperature resistant coating after polishing to form a coating with a thickness of about 1 mm, and obtaining the quartz crucible after natural drying.
[0052] Furthermore, the high temperature resistant coating is zirconium aluminate coating. In addition, during the polishing process of the transparent layer and the opaque layer of the quartz crucible, a polishing agent with a particle size of 0.5 μm is used.
[0053] Embodiment 3
[0054] This embodiment provides a method for preparing a high-density and high-thermal-conductivity quartz crucible, comprising the following steps:
[0055] S1. Put high-purity quartz sand, binder, nano-alumina and carbon nanotubes into a blender in a ratio of 8:1.5:0.5:0.2, and add an appropriate amount of deionized water to obtain an opaque layer mixture.
[0056] Furthermore, the purity of the high-purity quartz sand is not less than 99.9%, the particle size of the nano-alumina is less than 50 nm, and the content of the carbon nanotubes is 3% of the total mixture mass.
[0057] S2. The opaque layer mixture is pressed by a pressing device at a pressure of 35 MPa. After holding for 2 minutes, the mixture is demoulded and dried naturally to obtain an opaque layer.
[0058] S4. Put high-purity quartz powder and binder into a blender in a ratio of 9:1 and mix them, and add deionized water to obtain a transparent layer mixture.
[0059] S5. Evenly coating the transparent layer mixture on the inner wall of the opaque layer and pressing it with a pressing device, and drying it naturally to obtain an initial quartz crucible.
[0060] S6. Place the initial crucible in a closed cavity of a high-pressure isostatic pressing device, heat the cavity and apply an isostatic pressure of 180 MPa for 4 hours and gradually cool to room temperature at a cooling control rate of 25°C / hour.
[0061] Furthermore, during the cavity heating process, the temperature rises to 1500°C.
[0062] S7. Polishing the transparent layer and the opaque layer of the quartz crucible, and coating the layer with a high temperature resistant coating after polishing to form a coating with a thickness of about 2 mm, and obtaining the quartz crucible after natural drying.
[0063] Furthermore, the high temperature resistant coating is selected as a zirconium-based ceramic coating. In addition, during the polishing process of the transparent layer and the opaque layer of the quartz crucible, a polishing agent with a particle size of 0.5 μm is used.
[0064] Embodiment 4
[0065] This embodiment provides a method for preparing a high-density and high-thermal-conductivity quartz crucible, comprising the following steps:
[0066] S1. Put high-purity quartz sand, binder, nano-alumina and carbon nanotubes into a blender in a ratio of 8:1.5:0.5:0.2, and add an appropriate amount of deionized water to obtain an opaque layer mixture.
[0067] Furthermore, the purity of the high-purity quartz sand is not less than 99.9%, the particle size of the nano-alumina is less than 50 nm, and the content of the carbon nanotubes is 3% of the total mixture mass.
[0068] S2. The opaque layer mixture is pressed by a pressing device at a pressure of 35 MPa. After holding for 2 minutes, the mixture is demoulded and dried naturally to obtain an opaque layer.
[0069] S4. Put high-purity quartz powder and binder into a blender in a ratio of 9:1 and mix them, and add deionized water to obtain a transparent layer mixture.
[0070] S5. Evenly coating the transparent layer mixture on the inner wall of the opaque layer and pressing it with a pressing device, and drying it naturally to obtain an initial quartz crucible.
[0071] S6. Place the initial crucible in a closed cavity of a high-pressure isostatic pressing device, heat the cavity and apply an isostatic pressure of 150 MPa for 4 hours and gradually cool to room temperature at a cooling control rate of 25°C / hour.
[0072] Furthermore, during the cavity heating process, the temperature rises to 1500°C.
[0073] S7. Polishing the transparent layer and the opaque layer of the quartz crucible, and coating the layer with a high temperature resistant coating after polishing to form a coating with a thickness of about 2 mm, and obtaining the quartz crucible after natural drying.
[0074] Furthermore, the high temperature resistant coating is selected as a zirconium-based ceramic coating. In addition, during the polishing process of the transparent layer and the opaque layer of the quartz crucible, a polishing agent with a particle size of 0.5 μm is used.
[0075] Performance test experiment: The high-density and high-thermal-conductivity quartz crucible prepared by the method for preparing a high-density and high-thermal-conductivity quartz crucible provided in Examples 1 to 4 was tested for service life, compressive strength, flexural strength and porosity. The test data are as follows:
[0076] Table 1 is the performance test record of high-density and high-thermal-conductivity quartz crucible:
[0077]
[0078]
[0079] According to the performance test record of the high-density and high-thermal-conductivity quartz crucible in Table 1, Example 2 has the longest service life, reaching 2500 hours, showing excellent durability, followed by Example 4. Example 3 has the highest compressive strength, reaching 130 MPa, showing strong mechanical properties.
[0080] The compressive strength of Examples 3 and 4 is the highest, which is 130 MPa. The flexural strength of Example 4 is the highest, which is 60 MPa, reflecting good tolerance under bending and tensile stresses. The lowest porosity is in Examples 3 and 4, both of which are about 4%, indicating that the crucible structures of the two are the most compact. The lower the porosity, the better the compactness and thermal conductivity of the material.
[0081] In addition, as the carbon nanotube content increases (from 1% to 3%), the compressive strength and flexural strength gradually increase, especially reaching the best in Example 4.
[0082] In summary: in the preparation process of the quartz crucible, the present invention improves the mechanical strength and thermal conductivity of the crucible by adding nano-alumina, and the carbon nanotubes enhance the toughness and electrical conductivity of the material, ensuring the stability and reliability under high temperature conditions. After the initial crucible is prepared, the high-pressure isostatic pressing equipment is used, which can not only eliminate the pores inside the crucible and increase the density, but also promote the phase change of the material at high temperature, so that the crucible has excellent thermal conductivity and chemical stability. Therefore, the quartz crucible performs well in high-temperature experiments and material synthesis, meeting the needs of modern industry for high-performance ceramic materials.
[0083] Parts not involved in the present invention are the same as the prior art or can be implemented by the prior art. Although the embodiments of the present invention have been shown and described, it is understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high-density and high-thermal-conductivity quartz crucible, characterized in that: The following steps are involved: S1. Put high-purity quartz sand, binder, nano-alumina and carbon nanotubes into a blender in proportion and mix them, and add an appropriate amount of deionized water to obtain an opaque layer mixture; S2, pressing the opaque layer mixture using a pressing device, applying a pressure of 35 MPa, maintaining for 2 minutes, then demolding, and drying naturally to obtain an opaque layer; S4, putting high-purity quartz powder and a binder into a blender according to a certain proportion, and adding deionized water to obtain a transparent layer mixture; S5, uniformly coating the transparent layer mixture on the inner wall of the opaque layer and pressing it with a pressing device, and drying it naturally to obtain an initial quartz crucible; S6, placing the initial crucible into a closed cavity of a high-pressure isostatic pressing device, applying an isostatic pressure of 50 MPa-200 MPa while heating the cavity for 4 hours and gradually cooling to room temperature; S7. Polishing the transparent layer and the opaque layer of the quartz crucible, and coating the layer with a high temperature resistant coating after polishing to form a coating with a thickness of about 1-2 mm, and obtaining the quartz crucible after natural drying.
2. The method for preparing a high-density and high-thermal-conductivity quartz crucible according to claim 1, characterized in that: In the S1, the purity of the high-purity quartz sand is not less than 99.9%, the particle size of the nano-alumina is less than 50nm, and the content of the carbon nanotubes is 1-3% of the total mixture mass.
3. The method for preparing a high-density and high-thermal-conductivity quartz crucible according to claim 1, characterized in that: In S1, high-purity quartz sand, binder, nano-alumina and carbon nanotubes are put into a blender and mixed in a ratio of 8:1.5:0.5:0.
2.
4. The method for preparing a high-density and high-thermal-conductivity quartz crucible according to claim 1, characterized in that: In S3, high-purity quartz powder and binder are put into a mixer and mixed at a ratio of 9:
1.
5. The method for preparing a high-density and high-thermal-conductivity quartz crucible according to claim 1, characterized in that: In S6, the cooling control rate is 25°C / hour.
6. The method for preparing a high-density and high-thermal-conductivity quartz crucible according to claim 1, characterized in that: In S6, during the cavity heating process, the temperature rises to 1500°C-1700°C.
7. The method for preparing a high-density and high-thermal-conductivity quartz crucible according to claim 1, characterized in that: In S7, the high temperature resistant coating is selected from one of zirconium-based ceramic coating, zirconium aluminate coating and silicon nitride coating.
8. The method for preparing a high-density and high-thermal-conductivity quartz crucible according to claim 1, characterized in that: In the above S7, during the polishing process of the transparent layer and the opaque layer of the quartz crucible, a polishing agent with a particle size of 0.5 μm is used.
9. A high-density and high-thermal-conductivity quartz crucible, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.